NILAI-NILAI RELIGIUS DALAM CERPEN âLELAKI TUA YANG LEKAT DI DINDING MESJIDâ KARYA AKHMAD SEKHU - Arifin, Zainal (Universitas Muhammadiyah Surakarta, 2012)
This study aims at interpreting the religious values found in Lelaki Tua yang Lekat di Dindiding Mesjid short story. This study applies descriptive qualitative method. By using this method, the writer describes the religious values found in Lelaki Tua yang Lekat di Dinding Mesjid short story. The data are in the form of religious values discourse found in the text Lelaki Tua yang Lekat di Dindiding Mesjid short story written by Akhmad Sekhu. This literary work is published on the Paras Magazive Number. 101/Tahun IX/Maret 2012. The researcher uses content analysis, indept-interiewing, and questionanire for collecting the data. The writer also uses source triangulation for the data validity. The collected data were analysed by using interactive model. The results of the reserach show that first the mosque is used as 1) the place for praying together and learning islamic studies 2) the guideline for determining the Qibla direction; 3) the place for echoing the adzan sound so that the Moslem may begin to pray immediately; and 4) the place for reconciling among the people who have different beliefs. Second, the religiuos values found in the short story above refect that the Moslem is not only doing the prayer regularly but also upholding it in order their behaviours refer to Alquran and as-Sunah.